Identifying what services need to be improved by measuring the library's performance - Roslah , J.; Zainab, A.N. (2007)

(untitled)
Thi~ is an exploratory attempt to use a modified version of SERVPERF to assess user's sat!sjaction with the services provided by an [S09000:2000 certified library at a private Umv~rsity in Malaysia where measuring performance would be an integral part to ;Ontl~uously improve quality of services. The services being measured are grouped as rontlme, core and peripheral where staff and facilities interact with users directly and where usseerr' s optn. to.ns and expectations could be extracte. d Tt ntie c'It'ents are ~ndergraduates and postgraduates who use these services and facilities. The results Ide?tify . I services deem important to users of the library as well as the problem areas ;;ICh need improvements. A total of 274 students comprising 250 undergraduates and postgraduates form the sample. The respondents' ratings range on average between 3.13 and 4.36 on a 5-point scale, implying that the library is performing at an above average level. From 59 service attributes 2 are perceived as excellent, 20 attributes are Considered good, 31 are average and 4 services are rated as poor. A total of 16 services ~re rated below 50%, which form the priority list of services given priority in the library' s proposed action plan. The good and excellent services would continue to be monitored to maintain their performance.